DATA SCIENCE APPLICATION IN AGRICULTURE MARKETING (International Journal of Food and Nutritional Sciences, 2022)
In Indian Economy Agriculture plays vital role. India produces fruits & vegetables in huge percentage comparing to other countries. Though it is largest sector, suffers from calamities such as sudden climate change, floods, less water supply, monsoons, etc. Now Its time to apply data science tool in agricultural sector to promote farmers to use digital apps for best crop cultivation, make farmers more aware about their farms. Farmers always prefer traditional ways of farming from selecting seeds to till produce vegetables. Sometimes they misuse the fertilizers because they don’t know the right fertilizer for their soil. Data science is just one step ahead to assist farmers. Using Data science tool now farmers can cultivate crops successfully. Now its time to assist farmers using Data science tools for product selling. Despite of successful crop cultivation farmers faced many problems in product selling market because they didn’t receive correct values for their products, this situation leads to loss in farming or simply unsuccessfull farming. Now lets see how Data science applicable to break this long intermediatory agent chain for product supply.